Studies on mutagenic sensitivity of seeds of pummelo (Citrus maxima Merr.) - Sankaran, M; Kalaivanan, D; Gowda, Suni (Journal of Horticultural Sciences, 2021)
Mutation breeding is a key method of generating a large number of heritable variations. Effective dose (LD50) needs to be standardized for inducing sufficient variation in a crop. In the present study, seeds were irradiated with different doses of Gamma rays and found that 66.94 Gy could suppress germination close to 50 percent (LD50) in pummelo. This 60 Gy gamma dose can effectively be used for raising the mutant populations to identify a desirable mutation in pummelo.
Keywords: Gamma Irradiation; Germination; Gray (Gy) LD50; Mutation; Pummelo